2009
DOI: 10.1007/s12630-009-9132-8
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasound-assisted approach facilitates spinal anesthesia for total joint arthroplasty

Abstract: Purpose Spinal anesthesia can be challenging in patients undergoing total joint arthroplasty because of poorly palpable surface landmarks and age-related changes in the lumbar spine. We hypothesized that pre-procedural ultrasound imaging would be effective in identifying the lumbar intervertebral spaces and would provide an accurate measure of the depth to the intrathecal space. Methods Fifty patients undergoing elective total joint arthroplasty were recruited in this prospective descriptive study. Using a cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 28 publications
3
73
1
Order By: Relevance
“…In addition, using ultrasound may also reduce the number of attempts to place the block, thus improving patient satisfaction. 5,16,17 Recent studies in parturients who received epidural analgesia showed that the distance from the skin to the epidural space can be measured accurately in both normal and obese patients. 18,19 This may reduce the risk of accidental dural puncture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using ultrasound may also reduce the number of attempts to place the block, thus improving patient satisfaction. 5,16,17 Recent studies in parturients who received epidural analgesia showed that the distance from the skin to the epidural space can be measured accurately in both normal and obese patients. 18,19 This may reduce the risk of accidental dural puncture.…”
Section: Discussionmentioning
confidence: 99%
“…[14,22] Preoperative imaging with ultrasound may be useful in the application of spinal anesthesia and selection of anesthesia methods. [28,29] Therefore, the use of imaging techniques is likely to be helpful for patients with AS when NAA application is expected to be difficult. The use of ultrasound in NAA has been recently suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound in NAA has been recently suggested. [28] The advantages of easy positioning and absence of radiation exposure make USG preferable to fluoroscopy. However, USG was performed in only one patient in the literature we assessed, suggesting that there remains a great opportunity for preoperative assessment and application of USG in NAA for patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…The application of ultrasound technology provides some benefits to visualization of landmarks that are difficult to feel with surface anatomy in the presence of obesity or spinal abnormalities. 6,7 It also facilitates identifying the correct lumbar interspaces, as it has been shown repeatedly that palpation of the spine for identification of a particular lumbar vertebra is inaccurate even with experienced practitioners. [8][9][10] Nevertheless, teaching the use of ultrasound in guiding neuraxial blockade can be challenging, as new knowledge must be learned and new skills must be acquired.…”
Section: Discussionmentioning
confidence: 99%